2016
DOI: 10.1177/1096348016640588
|View full text |Cite
|
Sign up to set email alerts
|

A Tri-Method Approach to a Review of Adventure Tourism Literature: Bibliometric Analysis, Content Analysis, and a Quantitative Systematic Literature Review

Abstract: This article provides an objective, systematic, and integrated review of the Western academic literature on adventure tourism to discover the theoretical foundations and key themes underlying the field by combining three complementary approaches of bibliometric analysis, content analysis, and a quantitative systematic review. A total of 114 publications on adventure tourism were identified that revealed three broad areas of foci with adventure tourism research: (1) adventure tourism experience, (2) destination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
125
0
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 169 publications
(134 citation statements)
references
References 74 publications
1
125
0
8
Order By: Relevance
“…These results are coincident with bibliometric analyzes performed in different types of tourism; creative tourism [119], active tourism [120], adventure tourism [121], community-based tourism [122]; wine tourism [123], rural tourism [124], all these types of tourism depend on cultural and natural resources. Because they are specific types of tourism, the interest of researchers is lower than when tourism in general is investigated.…”
Section: Discussionsupporting
confidence: 82%
“…These results are coincident with bibliometric analyzes performed in different types of tourism; creative tourism [119], active tourism [120], adventure tourism [121], community-based tourism [122]; wine tourism [123], rural tourism [124], all these types of tourism depend on cultural and natural resources. Because they are specific types of tourism, the interest of researchers is lower than when tourism in general is investigated.…”
Section: Discussionsupporting
confidence: 82%
“…content analysis) tool that has gained prominence in the academic community (Biesenthal and Wilden, 2014), more recently in tourism and hospitality (Cheng et al, 2016). It interprets and visualizes complex text data by transforming "lexical co-occurrence information from natural language into semantic patterns in an unsupervised manner" through "two stages of extraction − semantic and relational" (Smith and Humphreys, 2006, p. 262).…”
Section: Content Analysismentioning
confidence: 99%
“…Furthermore, adventure activities require involvement, skills and performance (Cheng et al, 2016;Pomfret, 2006) and to experience a "rush" has lately been identified as key (Buckley, 2012). The thrill is the active participation by the consumer in naturalistic activity (Arnould, 2007) which leads to the feelings of sensation and flow (Csíkszentmihályi, 1990;Csíkszentmihályi & Rathunde, 1993) that are often sought in these experiences.…”
Section: Personalitymentioning
confidence: 99%
“…The representation of people as adventure seekers has become commonplace. Due to the increased attention to adventure activity (Pomfret & Bramwell, 2014), the potential for the development of experiences based on such activities has aroused increasing interest (Cheng, Edwards, Darcy, & Redfern, 2016). Since participation in adventurous activities often requires great effort and commitment, participation might not appeal to, or be attainable by everyone.…”
Section: Introductionmentioning
confidence: 99%